Notes on the identity of Leea setuligera and Leea talbotii (Vitaceae) - A., Amrutha; Pradeep, A. K. (Phytotaxa, 2023)
Leea talbotii is found to be conspecific with Leea setuligera, but not with Leea macrophylla as understood previously. A detailed description, photo plate and illustration of L. setuligera are provided, and the lectotype of L. talbotii and Leea mastersii var. siamensis is designated.